2012
DOI: 10.4103/2278-9626.105359
|View full text |Cite
|
Sign up to set email alerts
|

Determination of additional canals in maxillary first permanent molars in adult Nigerian population: Using in vivo and in vitro techniques

Abstract: Objective: To determine the prevalence of additional canals in maxillary first permanent molar in an adult population in Nigeria. Materials and Methods: This was a cross sectional study done using both in vivo and in vitro techniques. A total of 156 teeth were used; 50 for the in vivo and 106 for the in vitro study. Dental loupes and gentle troughing of the pulpal floor was done, to look for additional canal in the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a study, Oboro-Onuora et al . [ 12 ] analyzed the presence of additional canal in Nigerian population. Among 50 participants, they found that 34% of patients had MB2 in U16 and U26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, Oboro-Onuora et al . [ 12 ] analyzed the presence of additional canal in Nigerian population. Among 50 participants, they found that 34% of patients had MB2 in U16 and U26.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies indicate the prevalence of additional canal of one tooth. [ 2 7 8 12 13 14 15 16 ] Kim et al . [ 17 ] observed 976 participants of the mandibular first molar and found that 50.36% of participants had additional canals.…”
Section: Introductionmentioning
confidence: 99%